The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.13045/jar.2019.00304
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Acupuncture for Tennis Elbow

Abstract: This review analyzed randomized controlled trials and case reports to identify the effectiveness, and level of evidence showing that acupuncture treatment aids the recovery of patients with tennis elbow. A literature search was performed between 1 st to 10 th September, 2019 which used PubMed, the Cochrane library, the Korean databases Oriental Medicine Advanced Searching Integrated System, Korean Studies Information Service System to retrieve Korean and international studies. Amongst the 243 articles retrieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…[ 9 ] As aforementioned, ultrasound-guidance has been actively utilized for the treatment of shoulder pathology in medical fields. [ 19 , 20 ] It has also been effectively used in the treatment of lateral epicondylitis, acupuncture, [ 27 ] and pharmacopuncture. [ 28 ] There was also a previous study reporting that acupotomy showed a lower rate of recurrence than that in corticosteroid injections for the treatment of tennis elbow.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] As aforementioned, ultrasound-guidance has been actively utilized for the treatment of shoulder pathology in medical fields. [ 19 , 20 ] It has also been effectively used in the treatment of lateral epicondylitis, acupuncture, [ 27 ] and pharmacopuncture. [ 28 ] There was also a previous study reporting that acupotomy showed a lower rate of recurrence than that in corticosteroid injections for the treatment of tennis elbow.…”
Section: Discussionmentioning
confidence: 99%